Abstract 1122‐000197: Carotid‐Cavernous Fistula: Does Transcranial Duplex Worth Revisiting? - Mohamed Fahmy Doheim; Mohamed Mostafa (Stroke: Vascular and Interventional Neurology, 2021)
Introduction: Carotid‐cavernous fistula (CCF) represents a well‐known multifaceted diagnostic challenge starting from clinical presentation till angiography. This case presentation and literature review shed the light on the value of a bedside transcranial duplex (TCD) as a timely and a plausible screening tool. Methods: A case presentation and a brief literature review of CCF diagnosed via transcranial temporal window and made time to angiography shorter than the MRI brain. A review of literature was conducted for the timely diagnostic role of transtemporal TCD compared to transorbital US and an MRI brain. Results: Our case report showed the valuable role of the bedside TCD in diagnosing CCF. There is a limited number of studies which tackled the timely diagnostic role of transtemporal TCD compared to transorbital US and an MRI brain from door to angiography. Conclusions: A large‐sampled randomized controlled trial is needed for evaluating the actual utility of a bed side time and cost‐effective Transtemporal TCD vs other state‐of‐art non‐angiographic diagnostic modalities such as MRI, CT and transorbital US.